Somatotopy and temporal dynamics of sensorimotor interactions: evidence from double afferent inhibition. (16th April 2015) - Tamè, Luigi; Pavani, Francesco; Braun, Christoph; Salemme, Romeo; Farnè, Alessandro; Reilly, Karen T.
Abstract Moving and interacting with the world requires that the sensory and motor systems share information, but while some information about tactile events is preserved during sensorimotor transfer the spatial specificity of this information is unknown. Afferent inhibition (AI) studies, in which corticospinal excitability (CSE) is inhibited when a single tactile stimulus is presented before a transcranial magnetic stimulation pulse over the motor cortex, offer contradictory results regarding the sensory‐to‐motor transfer of spatial information. Here, we combined the techniques of AI and tactile repetition suppression (the decreased neurophysiological response following double stimulation of the same vs. different fingers) to investigate whether topographic information is preserved in the sensory‐to‐motor transfer in humans. We developed a double AI paradigm to examine both spatial (same vs. different finger) and temporal (short vs. long delay) aspects of sensorimotor interactions. Two consecutive electrocutaneous stimuli (separated by either 30 or 125 ms) were delivered to either the same or different fingers on the left hand (i.e. index finger stimulated twice or middle finger stimulated before index finger). Information about which fingers were stimulated was reflected in the size of the motor responses in a time‐constrained manner: CSE was modulated differently by same and different finger stimulation only when the two stimuli were separated by the short delay (P = 0.004). We demonstrate that the well‐known response of the somatosensory cortices following repetitive stimulation is mirrored in the motor cortex and that CSE is modulated as a function of the temporal and spatial relationship between afferent stimuli.